Optimising access to care for patients with heart and kidney diseases: A World Heart Federation and International Society of Nephrology white paper - Narula, Jagat; Butler, Javed; Chothia, Mogamat-Yazied; Bannerjee, Debasish; Jarraya, Faiçal; Ulasi, Ifeoma; Luyckx, Valerie (African Journal of Nephrology, 2025)
The clinical impact of diabetes medications including sodium-glucose cotransporter-2 (SGLT2) inhibitors, nonsteroidal mineralocorticoid receptor antagonists (MRAs) and glucagon-like peptide 1 receptor agonists (GLP-1 RAs) on cardiovascular (CV) and kidney disease outcomes has focused attention on the interrelatedness of kidney and heart health, both within and outside the context of diabetes. These conditions often co-exist in one individual resulting in frequent hospitalisations and premature deaths. Herein, we provide an updated comprehensive state-ofthe- art review, summarising the linkages between heart disease and kidney disease, the mechanisms connecting these conditions, common risk factors, management, implications for health systems, and the impact on patients, particularly in low resource settings. As experts representing the World Heart Federation (WHF) and International Society of Nephrology (ISN), we highlight areas of opportunity and provide recommendations on improving access to care for the growing numbers of patients with heart and kidney diseases with a focus on low-income and middleincome countries (LMICs).